Effects of fatigue induction on ground reaction force components, postural stability, and vertical jump performance in taekwondo athletes - Hyun, S.-H.; Kim, Y.-P.; Ryew, C.-C. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to investigate the effect of fatigue induction on ground reaction force (GRF) components, postural stability, and vertical jump performance in Taekwondo athletes. Method: Ten Taekwondo athletes (5 men, 5 women; mean age, 22.30 ± 2.62 years; mean height, 174.21 ± 9.20 cm; mean body weight, 67.28 ± 12.56 kg) participated in this study. Fatigue was induced by a short period of strenuous exercise performed on a motorized treadmill. The analyzed variables included vertical jump performance, static stability (mediolateral [ML], center of pressure [COP], anteroposterior [AP] COP, dCOPx, dCOPy, and COP area), postural stability index values (ML stability index [MLSI], AP stability index [APSI], vertical stability index [VSI], dynamic postural stability index [DPSI]), and GRF components (ML force, AP force, peak vertical force [PVF], and loading rate). To analyze the variables measured in this study, PASW version 22.0 was used to calculate the mean and standard deviation, while a paired t-test was used to evaluate the pre- versus post-fatigue results. Pearson's correlation coefficients among variables were also analyzed. The statistical significance level was set at a = .05. Results: Vertical jump performance decreased significantly after the induction of fatigue, while AP COP, dCOPx, COP area, APSI, VSI, and DPSI increased significantly. PVF and loading rate increased significantly after the induction of fatigue, while the postural stability variables (AP COP, dCOPy, COP area, APSI, VSI, DPSI) were similarly correlated with GRF components (PVF, loading rate) after fatigue was achieved (r = .600, R2 = 37%). Conclusion: These results suggest that the induction of fatigue can decrease postural stability and exercise performance of Taekwondo athletes during training and competition sessions.